2007
DOI: 10.1007/s10620-006-9262-6
|View full text |Cite
|
Sign up to set email alerts
|

Association Among C-Reactive Protein, Fatty Liver Disease, and Cardiovascular Risk

Abstract: Nonalcoholic fatty liver disease (NAFLD) is associated with several metabolic disturbances involving inflammation. Ultrasensitive C-reactive protein (uCRP), a marker of coronary heart disease and other chronic diseases, has not been investigated in NAFLD. We tested the relationship between uCRP and NAFLD in middle-aged asymptomatic subjects, independently of other metabolic disturbances associated with metabolic syndrome and cardiovascular risk. We compared 310 subjects with steatosis visible on ultrasound (ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2009
2009
2010
2010

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 40 publications
(34 reference statements)
1
22
0
Order By: Relevance
“…Third, the smoking data was collected by binary criteria in this study so the effects of smoking on metabolic syndrome components might be underestimated [35] . In summary, fatty liver and smoking were closely related to insulin resistance [1][2][3][4][5][6][7][8][9][11][12][13][14]16,[21][22][23]25,32] , and our study provided evidence that fatty liver and smoking had a synergistic effect on metabolic syndrome and its components, especially for triglyceride and HDL-C levels. We suggested that smoking cessation would have the great benefit of reducing the risk of metabolic syndrome, especially for subjects with fatty liver.…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations
“…Third, the smoking data was collected by binary criteria in this study so the effects of smoking on metabolic syndrome components might be underestimated [35] . In summary, fatty liver and smoking were closely related to insulin resistance [1][2][3][4][5][6][7][8][9][11][12][13][14]16,[21][22][23]25,32] , and our study provided evidence that fatty liver and smoking had a synergistic effect on metabolic syndrome and its components, especially for triglyceride and HDL-C levels. We suggested that smoking cessation would have the great benefit of reducing the risk of metabolic syndrome, especially for subjects with fatty liver.…”
Section: Discussionmentioning
confidence: 55%
“…While these studies provided evidence that smoking increased plasma TG and decreased HDL-C levels, most of these studies did not control potential confounding factors. Fatty liver also increased the risk of dyslipidemia such as hypertriglyceridemia and decreased HDL-C [3] . In our study, after controlling for confounding factors such as age, gender, drinking habit, and physical activity, the ORs for hypertriglyceridemia in subjects remained high: group 2 [fatty liver (-)/smoking (+)] 2.4 (95% CI: 1.8-3.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fasting adiponectin is inversely correlated with hepatic fat content in healthy non-diabetic subjects (31,33) but non-significantly in patients with type 2 diabetes mellitus (n = 10) (31). TNF-a, IL-6 and CRP may contribute to the inflammatory CVD milieu, predisposing to atherosclerosis and CVD (34)(35)(36). On the contrary, studies in both humans and animals (23,37) have revealed both anti-inflammatory (23) and antithrombotic (37) properties of adiponectin, enabling a protective association between adiponectin and CVD (38).…”
Section: Inflammationmentioning
confidence: 99%